Effect of intake length on flow interactions in a coupled compact intake-fan in crosswind - Lobuono, Luca; MacManus, David G.; Christie, Robert (American Institute of Aeronautics and Astronautics (AIAA), 2025)
More compact and short intakes can be a key enabler for the design of Ultra-High Bypass Ratio (UHBR) large civil aero engines. Under key design conditions such as crosswind significant flow distortion at the fan face can adversely affect the performance and engine compatibility. Shorter intakes may result in stronger intake-fan aerodynamic coupling, and the resulting unsteady interactions currently remain insufficiently understood. This study investigates how the intake length and crosswind direction can affect the intake-fan unsteady aerodynamics and distortion. Two computational models are used: a steady Reynolds-Averaged Navier-Stokes method with an Immersed Boundary Method with Smeared Geometry (RANS-IBMSG), and a time resolved fully coupled model (URANS-TRF). Swirl distortion is quantified in the relative frame of reference using a blade tracking method based on blade incidence angle. For the combination of research fan and intake analysed, the findings show that the fan proximity can reduce the onset of gross separation for shorter intake designs. This effect enables a reduction of intake length by about 25% while still meeting a crosswind operating condition requirement. In general, the RANS-IBMSG method predicts the main characteristics of the onset of gross intake separation and is in good agreement with the unsteady URANS-TRF simulations. Based on the unsteady simulations, a gross separation on the intake surface occurred at a lower crosswind velocity for the co-rotating configuration compared to the counter-rotating case for the research fan and intake studied. The RANS-IBMSG method does not capture some of the aerodynamic features responsible for differences between counter- and co-rotating configurations. Overall, while low-order fan models are useful for early-stage intake design evaluations, coupled unsteady simulations are required to fully capture the effects of crosswind direction and intake-fan interactions.